FEMALE SEX WORKERS’ ATTITUDES TOWARD HIV TESTING: A STUDY AMONG INDIRECT SEX WORKERS IN BANTUL, YOGYAKARTA, INDONESIA - Dhesi Ari Astuti; Moh. Hakimi; Andari Wuri Astuti; Dyah Anantalia Widyastari; Doni Marisi Sinaga (Belitung Nursing Journal, 2016)
Background: HIV prevalence among female sex workers in Indonesia is among the highest in Asia after Papua New Guinea and Malaysia. Indirect sex workers posed a heightened risk of HIV infection compared to direct sex workers because they usually earn less than their direct counterpart and have lower bargaining power in condom use. Objective: This study aims to examine the factors influencing indirect sex workers’ attitudes toward HIV testing. Methods: This study employed a quantitative method with a cross-sectional approach involved 67 indirect sex workers from massage parlors and beauty salons in Bantul district. Descriptive analysis of respondents’ attitude, perceive threat and expectation was drawn from Health Belief Model Theory. Results: The majority of indirect sex workers had positive attitude towards HIV testing. They are aware to the importance of condom in every commercial sex works, but the majority believe themselves were not susceptible to HIV-AIDS due to their preference to healthy-looking clients to serve sex. Personal expenses to visit the health center for HIV testing are less considered compared to public opinion and discrimination. Peers encouraged the workers to get tested. Disseminating HIV/AIDS information to sex workers through media and mobile phone are not successful. Conclusion: The findings of the study carrying an expectation that when individuals’ attitudes toward HIV testing are positive, the likelihood of getting themselves tested would also be higher. Since the perception is driven by information as stimulus, it is important to provide continuous information to create stimulus which eventually will influence their perception.